(untitled) (Hekima Review, 2016)
In the Catholic Church, the main goals of marriage are love and procreation. All other goals flow from these two. In the African context, it seems that the latter is emphasized more than the former to the extent that, sometimes, procreation as a goal of marriage overshadows love. This explains why most childless African Christian couples suffer social pressure and stigma for their inability to conceive. African theologians have looked at the matter but often with divided opinions: some leaning more towards the African traditional view while others towards the Catholic teaching. While acknowledging the tough situation that most African Christian childless couples go through, this article argues that altering the Christian teaching on marriage to suit the African tradition perspective would not in itself solve the problem. The article contends that the solution can be found in the Christian teaching itself while building on some aspects of African traditional marriage